Leaderless adaptive output feedback consensus approach for one-sided Lipschitz multi-agents. Issue 13 (September 2020) - Rehman, Ateeq ur; Rehan, Muhammad; Iqbal, Naeem; Waris, Muhammad Zohaib
Abstract: This paper addresses the relative-output feedback adaptive consensus protocol for one-sided Lipschitz (OSL) nonlinear agents with an undirected graph topology. Adaptive control methodology is employed to avoid the restriction of the requirement of global information of the graph topology to all agents for computing a coupling weight. Novel design conditions, including the necessary and sufficient conditions for the main design approach, by application of decoupling technique for consensus protocol formulation of OSL systems, are presented to evaluate the consensus protocol gains. A distinctive feature of the present work is the development of adaptive output feedback consensus protocol to avoid the state availability requirement in the existing works, by application of an edge-based consensus protocol, Lyapunov theory, graph topology, and nonlinearity bounds. The proposed approach is less conservative and more efficient than existing methods as it can be applied to a broader class of nonlinear systems with large Lipschitz constant. The validity of the proposed technique is verified through numerical simulations of six mobile agents and a practical application of unmanned air vehicles.